Ehlers-Danlos syndrome, clotting disorders and muscular dystrophy. Issue 11 (November 1989) - Bertin, P; Treves, R; Julia, A; Gaillard, S; Desproges-Gotteron, R
Abstract : Ehlers-Danlos syndrome includes 11 distinct entities. The diversity of this collagen dysplasia and its combination with other abnormalities make it difficult to understand physiopathologically. A case of Ehlers-Danlos syndrome is reported, which is novel owing to its combination with clotting abnormalities and especially with muscular dystrophy. To our knowledge this has not previously been reported. The patient was a young man aged 16 years who presented with Ehlers-Danlos syndrome satisfying Perelman's diagnostic criteria. His father and two brothers had comparable clinical symptoms, but his mother and sister were healthy. The four male subjects had an increased cephalin-kaolin time, reduced levels of factor VIII and Willebrand's factor (but without haemophilia A or Willebrand's disease), and, especially, an abnormal platelet ATP secretion. The proband alone had muscular disease with bilateral quadriceps fatigability and amyotrophy. The muscle enzyme levels were greatly increased, the electromyographic trace was myogenic, and the biopsy showed severe muscular dystrophy. This new observation poses the problem of the relation between clotting abnormalities and collagen abnormalities in the Ehlers-Danlos syndrome. It is difficult to classify this case within any of the 11 known types because of its muscular manifestations. It may perhaps be a fortuitous combination or an extension of the nosological framework of this syndrome.